Historical defence capability analysis: applying the defence lines of development retrospectively - Fisher, Richard (Taylor & Francis, 2023)
The Defence Lines of Development (DLOD) used by the Ministry of Defence encompass all elements of military capability. Historical study of military capabilities does not use a similar or equivalent model. Richard Fisher describes how the current DLOD model can be used to analyse historical capabilities. He provides an objective approach to any comparison by capturing the training, equipment, personnel, information, doctrine and concepts, organisation, infrastructure and logistics requirements of machine gunnery in the British Army from the First World War to the 1960s, as a case study to demonstrate the method.
Keywords: capability; history; small arms; machine guns; analysis; defence lines of development